Endovascular treatment under laparotomy with n-butyl-2-cyanoacrylate in a pediatric traumatic aortic injury: a case report - Hikaru Oe; Shimpei Ikeda; Takahiko Mine; Yoshiaki Hara (Journal of Cardiothoracic Surgery)
Abstract Background The Society for Vascular Surgery (SVS) guidelines recommend thoracic endovascular aortic repair (TEVAR) for blunt traumatic aortic injuries (BTAI) in adults, especially BTAI grades II to IV. TEVAR is increasingly performed for BTAI in children and adolescents; however, reports on treatment strategies are limited. Percutaneous routes for stenting may not be available in children with anatomically small vessel diameters, and the indications for stent grafts are challenging because of the steep aortic angle. Case presentation We report a case of TEVAR for BTAI performed under laparotomy with n-butyl-2-cyanoacrylate (NBCA) injection in an adolescent patient. The patient was a 13-year-old male who sustained injuries due to a fall and presented with severe hypoxia and shock on admission. Computed tomography (CT) showed a thoracic aortic injury with a pseudoaneurysm (SVS grade III) and bilateral pulmonary contusions. We planned to perform TEVAR after venovenous extracorporeal membrane oxygenation (ECMO); however, because of the small diameters of the bilateral common femoral arteries, we placed a stent graft through the left common iliac artery under laparotomy. In addition, the proximal landing zone of the stent graft to the thoracic pseudoaneurysm was short, and we filled the pseudoaneurysm with NBCA after deploying the stent graft to prevent endoleaks. Subsequent CTs showed no endoleaks, and the patient was discharged on day 110. Conclusions We report a case of TEVAR in a 13-year-old boy who underwent laparotomy with NBCA injection into a pseudoaneurysm. This method may be useful as an alternative when percutaneous access is not available, and the proximal landing zone cannot be reached.